The effect of the fibrocalcific pathological process on aortic valve stenosis in female patients: a finite element study. (1st March 2022) - Karnibad, Maya; Sharabi, Mirit; Lavon, Karin; Morany, Adi; Hamdan, Ashraf; Haj-Ali, Rami
Abstract: Calcific aortic valve disease (CAVD) is the most common heart valvular disease in the developed world. Most of the relevant research has been sex-blind, ignoring sex-related biological variables and thus under-appreciate sex differences. However, females present pronounced fibrosis for the same aortic stenosis (AS) severity compared with males, who exhibit more calcification. Herein, we present a computational model of fibrocalcific AV, aiming to investigate its effect on AS development. A parametric study was conducted to explore the influence of the total collagen fiber volume and its architecture on the aortic valve area (AVA). Towards that goal, computational models were generated for three females with stenotic AVs and different volumes of calcium. We have tested the influence of fibrosis on various parameters as fiber architecture, fibrosis location, and transvalvular pressure. We found that increased fiber volume with a low calcium volume could actively contribute to AS and reduce the AVA similarly to high calcium volume. Thus, the computed AVAs for our fibrocalcific models were 0.94 and 0.84 cm 2 and the clinical (Echo) AVAs were 0.82 and 0.8 cm 2 . For the heavily calcified model, the computed AVA was 0.8 cm 2 and the clinical AVA was 0.73 cm 2 . The proposed models demonstrated how collagen thickening influence the fibrocalcific-AS process in female patients. These models can assist in the clinical decision-making process and treatment development in valve therapy for female patients.